Role of human Kallistatin in glucose and energy homeostasis in mice - Leontine Sandforth; Sebastian Brachs; Julia Reinke; Diana Willmes; Gencer Sancar; Judith Seigner; David Juarez-Lopez; Arvid Sandforth; Jeffrey D. McBride; Jian-Xing Ma; Sven Haufe; Jens Jordan; et al. (Molecular Metabolism, 2024)
Objective: Kallistatin (KST), also known as SERPIN A4, is a circulating, broadly acting human plasma protein with pleiotropic properties. Clinical studies in humans revealed reduced KST levels in obesity. The exact role of KST in glucose and energy homeostasis in the setting of insulin resistance and type 2 diabetes is currently unknown. Methods: Kallistatin mRNA expression in human subcutaneous white adipose tissue (sWAT) of 47 people with overweight to obesity of the clinical trial “Comparison of Low Fat and Low Carbohydrate Diets With Respect to Weight Loss and Metabolic Effects (B-SMART)” was measured. Moreover, we studied transgenic mice systemically overexpressing human KST (hKST-TG) and wild type littermate control mice (WT) under normal chow (NCD) and high-fat diet (HFD) conditions. Results: In sWAT of people with overweight to obesity, KST mRNA increased after diet-induced weight loss. On NCD, we did not observe differences between hKST-TG and WT mice. Under HFD conditions, body weight, body fat and liver fat content did not differ between genotypes. Yet, during intraperitoneal glucose tolerance tests (ipGTT) insulin excursions and HOMA-IR were lower in hKST-TG (4.42 ± 0.87 AU, WT vs. 2.20 ± 0.27 AU, hKST-TG, p < 0.05). Hyperinsulinemic euglycemic clamp studies with tracer-labeled glucose infusion confirmed improved insulin sensitivity by higher glucose infusion rates in hKST-TG mice (31.5 ± 1.78 mg/kg/min, hKST-TG vs. 18.1 ± 1.67 mg/kg/min, WT, p < 0.05). Improved insulin sensitivity was driven by reduced hepatic insulin resistance (clamp hepatic glucose output: 7.7 ± 1.9 mg/kg/min, hKST-TG vs 12.2 ± 0.8 mg/kg/min, WT, p < 0.05), providing evidence for direct insulin sensitizing effects of KST for the first time. Insulin sensitivity was differentially affected in skeletal muscle and adipose tissue. Mechanistically, we observed reduced Wnt signaling in the liver but not in skeletal muscle, which may explain the effect. Conclusions: KST expression increases after weight loss in sWAT from people with obesity. Furthermore, human KST ameliorates diet-induced hepatic insulin resistance in mice, while differentially affecting skeletal muscle and adipose tissue insulin sensitivity. Thus, KST may be an interesting, yet challenging, therapeutic target for patients with obesity and insulin resistance.